Determining Students' Nutritional Status Using Mamdani Fuzzy Logic Method - Dyah Muslihah; Fatchul Arifin (PT FORMOSA CENDEKIA GLOBAL, 2023)
Nutritional status is a body condition as a result of food consumption or a measure of the success of nutritional fulfillment; there is a balance between the amount of nutrient intake and the amount required by the body for a variety of biological functions such as physical growth, development, activity or productivity, health maintenance, and others. Children’s nutritional status is indicated by weight and height [6]. Theoretically, nutritional status can be determined based on Anthropometric standards. Fuzzy logic is a method to show problems from input to expected output [4]. The Mamdani fuzzy method is one of the methods of the fuzzy inference system. This research uses Matlab R2021b software to apply the fuzzy method